Talent Management and Its role in reaching The Golden Position: An Exploratory Study In Al Rayyan Dairy Production - Shritham, Muslim Kheraibet (The Gulf Economist, 2023)
This study aims to providing a theoretical and intellectual framework regarding the study variables, and to identify the nature of the relationship between talent management and the golden summit reaching. In addition to provide the Iraqi libraries with a study that addresses the most important topics (talent management and the Golden Summit). The study population was established in 2014 in Basra Governorate in Iraq. The sample company includes more than (250) male and female workers in various specializations. The researcher chose a stratified random sample of (62) and the research relied on the descriptive analytical method. Field data was collected through a questionnaire that was constructed and developed to consisted of two parts, the first part of which was about talent management, while the Second part contained the golden status. To analyze the data using the Statistical Package for the Social Sciences program (SPSS). The research reached a set of results, the most important of which are: There is a lack In applying the criteria for testing creativity and intelligence in order to discover innate talents during the process of attracting talents. Although Al Rayyan Company has a golden status in the sector in which it operates, it still does not have a talented workforce. Talent management at Al Rayyan Company needs great attention from senior management in how to apply its dimensions in a scientific and practical manner.